Explaining Populist Attitudes: The Impact of Policy Discontent and Representation - Robert A. Huber; Michael Jankowski; Carsten Wegscheider (Politische Vierteljahresschrift, 2022)
Recently, scholars of populism have increasingly started to theorise and capture susceptibility to populism at the individual level. Most of these studies, however, focus on the consequences of populist attitudes on political behaviour. Less attention has been paid to the question of which citizens have high levels of populist attitudes and why. While some scholars argue that populist attitudes more resemble an unchangeable personality trait, meaning that individuals may be more or less populist, others argue that it is a~response to outside grievances or discontent. The latter suggests that levels of populist attitudes are dynamic and may change if grievances are addressed (or remain unaddressed). We contribute to this literature by asking how discontent fuelled by unfulfilled policy preferences affects the level of populist attitudes. Following the conception of populism as a~thin-centred ideology, we argue that high levels of populist attitudes are not connected with certain issues per se. Rather, our argument is that people are more populist when they feel poorly represented on policy issues that they care strongly about. This argument provides an explanation for the observation that even voters of non-populist parties sometimes show high levels of populist attitudes. We test the impact of policy discontent on populist attitudes using data from the GLES 2021 Pre-Election Cross Section survey by combining information on citizens' issue specific discontent with the perceived salience of respective issues. The results are in line with our expectations: Individuals with higher policy discontent are more populist.
Keywords: 320; Populist attitudes; Policy discontent; Representation; Open Science; Germany